2019
DOI: 10.1101/665620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-molecule control of super-Mendelian inheritance in gene drives

Abstract: By surpassing the 50% inheritance limit of Mendel's law of independent assortment, CRISPR-based gene drives have the potential to fight vector-borne diseases or suppress crop pests. However, contemporary gene drives could spread unchecked, posing safety concerns that limit their use in both laboratory and field settings. Current technologies also lack chemical control strategies, which could be applied in the field for dose, spatial and temporal control of gene drives. We describe in Drosophila the first gene-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Two cases are informative in this regard. First, e-CHACR-e did not copy when combined with Cas9, although in a split-drive configuration, without the Cas9-targeting gRNA, it exhibited modest drive ($60%) (Ló pez Del Amo et al, 2019). When combined with a cleavage-resistant Cas9* form, however, e-CHACR-e drove at levels similar to those in the split-drive experiments.…”
Section: Drive Performance Of Drive and Neutralization Systemsmentioning
confidence: 70%
“…Two cases are informative in this regard. First, e-CHACR-e did not copy when combined with Cas9, although in a split-drive configuration, without the Cas9-targeting gRNA, it exhibited modest drive ($60%) (Ló pez Del Amo et al, 2019). When combined with a cleavage-resistant Cas9* form, however, e-CHACR-e drove at levels similar to those in the split-drive experiments.…”
Section: Drive Performance Of Drive and Neutralization Systemsmentioning
confidence: 70%
“…Briefly, we fused Escherichia coli dihydrofolate reductase (DHFR) domains to SpCas9 to promote its rapid proteasomal degradation in the absence of the stabilizing small molecule trimethoprim (TMP) 29,30 . We showed that TMP addition to the fruit fly diet stabilized our modified SpCas9 (DD2-Cas9) and allowed super-Mendelian inheritance control of a CopyCat active genetic element 28 .…”
Section: Gene Drive Process Reveals Predictable Resistant Allele Formmentioning
confidence: 98%
“…We recently developed a small-molecule-controlled system for use in active genetics approaches including CRISPR-based gene-drive systems 28 . Briefly, we fused Escherichia coli dihydrofolate reductase (DHFR) domains to SpCas9 to promote its rapid proteasomal degradation in the absence of the stabilizing small molecule trimethoprim (TMP) 29,30 .…”
Section: Gene Drive Process Reveals Predictable Resistant Allele Formmentioning
confidence: 99%
“…Since we observed improved activity when using scaffold variants in both Culex quinquefasciatus and Drosophila melanogaster , we wondered whether these variants could be effectively used in a gene-drive strategy, and whether they would improve efficiency in these genetic systems. To test these hypotheses, we employed a split-gene-drive strategy (aka CopyCat) in Drosophila 19,42,44,45 . Briefly, a CopyCat element consists of a transgene containing a gRNA element (and a GFP marker) flanked by two homology arms, which match the targeted locus sequence on each side of a cut site generated by the gRNA within the transgene ( Fig.…”
Section: Grna Scaffold Variants Improve Gene Drive Efficiency In Drosmentioning
confidence: 99%
“…To compare transgenesis efficiency at the white gene in Drosophila using the "Loop" modification versus the original construct ( Fig. 4 ), each construct was separately injected into a Vasa -Cas9 line generated in our laboratory 42 (same line used for gene drive experiments). For these experiments, we waited until the injected G0 embryos became adults, then single-pair crossed them to white-eye mutant individuals.…”
Section: Drosophila Transgenesis Experimentsmentioning
confidence: 99%